Penerapan Proses Employer Branding Pada Perusahaan E-Commerce (Studi Kasus pada Shopee Indonesia) - Radhinda, Pitaloka Ayu (Universitas Brawijaya, 2020)
The success of a company depends on its branding managed human resources. Therefore it is important for the company to pay attention to the image or image attached to the company. This article seeks to find out how employer branding is implemented at the e-commerce company Shopee Indonesia. This research was conducted using a qualitative approach and a case study research method. Data collected from interviews with key informants throughout 2018. The results stated that the application of employer branding in Shopee Indonesia is carried out through a program that refers to the company's vision and mission, personality, and core value. Employer branding program refers to the Employee Value Proposition (EVP) strategy of internal marketing and external marketing. Shopee packages the program through #LifeAtShopee which is run by several departments within Shopee. Employer branding programs at Shopee are not only to attract potential employees and keep employees as company assets, but also to influence Shopee's image in the eyes of the public externally and internally.